Induced smectic phase in binary mixtures of twist-bend nematogens - Knežević, Anamarija; Dokli, Irena; Sapunar, Marin; Šegota, Suzana; Baumeister, Ute; Lesac, Andreja (Beilstein Journal of Nanotechnology, 2018)
The investigation of liquid crystal (LC) mixtures is of great interest in tailoring material properties for specific applications. The recent discovery of the twist-bend nematic phase (NTB) has sparked great interest in the scientific community, not only from a fundamental viewpoint, but also due to its potential for innovative applications. Here we report on the unexpected phase behaviour of a binary mixture of twist-bend nematogens. A binary phase diagram for mixtures of imino-linked cyanobiphenyl (CBI) dimer and imino-linked benzoyloxy-benzylidene (BB) dimer shows two distinct domains. While mixtures containing less than 35 mol % of BB possess a wide temperature range twist-bend nematic phase, the mixtures containing 55–80 mol % of BB exhibit a smectic phase despite that both pure compounds display a Iso–N–NTB–Cr phase sequence. The phase diagram shows that the addition of BB of up to 30 mol % significantly extends the temperature range of the NTB phase, maintaining the temperature range of the nematic phase. The periodicity, obtained by atomic force microscopy (AFM) imaging, is in the range of 6–7 nm. The induction of the smectic phase in the mixtures containing 55–80 mol % of BB was confirmed using polarising optical microscopy (POM), differential scanning calorimetry (DSC) and X-ray diffraction. The origin of the intercalated smectic phase was unravelled by combined spectroscopic and computational methods and can be traced to conformational disorder of the terminal chains. These results show the importance of understanding the phase behaviour of binary mixtures, not only in targeting a wide temperature range but also in controlling the self-organizing processes.
Keywords: binary mixture; liquid crystals; smectic phase induction; temperature-dependent FTIR; twist-bend nematogen

U.S. Patent - Goldmacher, J. E.; Castellano, J. A. (1970)

(untitled) - Cestari, M.; Diez-Berart, S.; Dunmur, D. A.; Ferrarini, A.; de La Fuente, M. R.; Jackson, D. J. B.; Lopez, D. O.; Luckhurst, G. R.; Perez-Jubindo, M. A.; Richardson, R. M.; Salud, J.; Timimi, B. A.; et al. (Phys. Rev. E, 2011)

(untitled) - Šepelj, M.; Lesac, A.; Baumeister, U.; Diele, S.; Nguyen, H. L.; Bruce, D. W. (J. Mater. Chem., 2007)

(untitled) - Tripathi, C. S. P.; Losada-Pérez, P.; Glorieux, C.; Kohlmeier, A.; Tamba, M.-G.; Mehl, G. H.; Leys, J. (Phys. Rev. E, 2011)

(untitled) - Parthasarathi, S.; Rao, D. S. S.; Palakurthy, N. B.; Yelamaggad, C. V.; Krishna Prasad, S. (J. Phys. Chem. B, 2016)

(untitled) - Paterson, D. A.; Abberley, J. P.; Harrison, W. T. A.; Storey, J. M. D.; Imrie, C. T. (Liq. Cryst., 2017)

(untitled) - Henderson, P. A.; Imrie, C. T. (Liq. Cryst., 2011)

(untitled) - Dawood, A. A.; Grossel, M. C.; Luckhurst, G. R.; Richardson, R. M.; Timimi, B. A.; Wells, N. J.; Yousif, Y. Z. (Liq. Cryst., 2016)

(untitled) - Archbold, C. T.; Davis, E. J.; Mandle, R. J.; Cowling, S. J.; Goodby, J. W. (Soft Matter, 2015)

(untitled) - Adlem, K.; Čopič, M.; Luckhurst, G. R.; Mertelj, A.; Parri, O.; Richardson, R. M.; Snow, B. D.; Timimi, B. A.; Tuffin, R. P.; Wilkes, D. (Phys. Rev. E, 2013)

(untitled) - López, D. O.; Robles-Hernández, B.; Salud, J.; de la Fuente, M. R.; Sebastián, N.; Diez-Berart, S.; Jaen, X.; Dunmur, D. A.; Luckhurst, G. R. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Ramou, E.; Ahmed, Z.; Welch, C.; Karahaliou, P. K.; Mehl, G. H. (Soft Matter, 2016)

(untitled) - Park, J. W.; Bak, C. S.; Labes, M. M. (J. Am. Chem. Soc., 1975)

(untitled) - Sugisawa, S.-y.; Tabe, Y. (Soft Matter, 2016)

(untitled) - Szabon, J.; Diele, S. (Cryst. Res. Technol., 1982)

(untitled) - Ivšić, T.; Vinković, M.; Baumeister, U.; Mikleušević, A.; Lesac, A. (RSC Adv., 2016)

(untitled) - Ivšić, T.; Baumeister, U.; Dokli, I.; Mikleušević, A.; Lesac, A. (Liq. Cryst., 2017)

(untitled) - Dawood, A. A.; Grossel, M. C.; Luckhurst, G. R.; Richardson, R. M.; Timimi, B. A.; Wells, N. J.; Yousif, Y. Z. (Liq. Cryst., 2017)

(untitled) - Humphries, R. L.; James, P. G.; Luckhurst, G. R. (Symp. Faraday Soc., 1971)

(untitled) - Mandle, R. J.; Goodby, J. W. (Chem. – Eur. J., 2016)

(untitled) - Mandle, R. J. (Soft Matter, 2016)

(untitled) - Chen, D.; Nakata, M.; Shao, R.; Tuchband, M. R.; Shuai, M.; Baumeister, U.; Weissflog, W.; Walba, D. M.; Glaser, M. A.; Maclennan, J. E.; Clark, N. A. (Phys. Rev. E, 2014)

(untitled) - Borshch, V.; Kim, Y.-K.; Xiang, J.; Gao, M.; Jákli, A.; Panov, V. P.; Vij, J. K.; Imrie, C. T.; Tamba, M. G.; Mehl, G. H.; Lavrentovich, O. D. (Nat. Commun., 2013)

(untitled) - Tuchband, M. R.; Shuai, M.; Graber, K. A.; Chen, D.; Zhu, C.; Radzihovsky, L.; Klittnick, A.; Foley, L. M.; Scarbrough, A.; Porada, J. H.; Moran, M.; Yelk, J.; et al. (arXiv [cond-mat.soft], 2017)

(untitled) - Tuchband, M. R.; Shuai, M.; Graber, K. A.; Chen, D.; Radzihovsky, L.; Klittnick, A.; Foley, L.; Scarbrough, A.; Porada, J. H.; Moran, M.; Korblova, E.; Walba, D. M.; et al. (arXiv [cond-mat.soft], 2015)

(untitled) - Gorecka, E.; Salamonczyk, M.; Zep, A.; Pociecha, D.; Welch, C.; Ahmed, Z.; Mehl, G. H. (Liq. Cryst., 2015)

(untitled) - Gorecka, E.; Vaupotič, N.; Zep, A.; Pociecha, D.; Yoshioka, J.; Yamamoto, J.; Takezoe, H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Emsley, J. W.; Lelli, M.; Lesage, A.; Luckhurst, G. R. (J. Phys. Chem. B, 2013)

(untitled) - Paterson, D. A.; Gao, M.; Kim, Y.-K.; Jamali, A.; Finley, K. L.; Robles-Hernández, B.; Diez-Berart, S.; Salud, J.; de la Fuente, M. R.; Timimi, B. A.; Zimmermann, H.; Greco, C.; et al. (Soft Matter, 2016)

(untitled) - Sebastián, N.; Robles-Hernández, B.; Diez-Berart, S.; Salud, J.; Luckhurst, G. R.; Dunmur, D. A.; López, D. O.; de la Fuente, M. R. (Liq. Cryst., 2017)

(untitled) - Mandle, R. J.; Davis, E. J.; Archbold, C. T.; Voll, C. C.; Andrews, J. L.; Cowling, S. J.; Goodby, J. W. (Chem. – Eur. J., 2015)

(untitled) - Mandle, R. J.; Goodby, J. W. (Soft Matter, 2016)

(untitled) - Tamba, M. G.; Salili, S. M.; Zhang, C.; Jákli, A.; Mehl, G. H.; Stannarius, R.; Eremin, A. (RSC Adv., 2015)

(untitled) - Attard, G. S.; Date, R. W.; Imrie, C. T.; Luckhurst, G. R.; Roskilly, S. J.; Seddon, J. M.; Taylor, L. (Liq. Cryst., 1994)

(untitled) - Imrie, C. T. (Liq. Cryst., 2006)

(untitled) - Yeap, G.-Y.; Hng, T.-C.; Yeap, S.-Y.; Gorecka, E.; Ito, M. M.; Ueno, K.; Okamoto, M.; Mahmood, W. A. K.; Imrie, C. T. (Liq. Cryst., 2009)

(untitled) - Singh, S.; Singh, H.; Tandon, P.; Rao, N. V. S.; Ayala, A. P. (Vib. Spectrosc., 2017)

(untitled) - Ogawa, R.; Miwa, Y.; Kutsumizu, S. (J. Phys. Chem. B, 2015)

(untitled) - Mantsch, H. H.; McElhaney, R. N. (Chem. Phys. Lipids, 1991)

(untitled) - Saupe, A. (Mol. Cryst. Liq. Cryst., 1972)

(untitled) - Ogawa, R.; Miwa, Y.; Sumita, M.; Saito, K.; Kutsumizu, S. (Liq. Cryst., 2015)

(untitled) - Bardeau, J.-F.; Parikh, A. N.; Beers, J. D.; Swanson, B. I. (J. Phys. Chem. B, 2000)

(untitled) - Kutsumizu, S.; Kato, R.; Yamada, M.; Yano, S. (J. Phys. Chem. B, 1997)

(untitled) - Galbiati, E.; Zerbi, G. (J. Chem. Phys., 1987)

(untitled) - Lewis, R. N. A. H.; McElhaney, R. N. (Chem. Phys. Lipids, 1998)

(untitled) - Nilsson, A.; Holmgren, A.; Lindblom, G. (Chem. Phys. Lipids, 1994)

(untitled) - Šegota, S.; Vojta, D.; Pletikapić, G.; Baranović, G. (Chem. Phys. Lipids, 2015)

(untitled) - Ahlrichs, R.; Bär, M.; Häser, M.; Horn, H.; Kölmel, C. (Chem. Phys. Lett., 1989)

(untitled) - Eichkorn, K.; Treutler, O.; Öhm, H.; Häser, M.; Ahlrichs, R. (Chem. Phys. Lett., 1995)

(untitled) - Imrie, C. T.; Henderson, P. A. (Chem. Soc. Rev., 2007)

(untitled) - Archbold, C. T.; Andrews, J. L.; Mandle, R. J.; Cowling, S. J.; Goodby, J. W. (Liq. Cryst., 2017)

(untitled) - Goodby, J. W.; Mandle, R. J.; Davis, E. J.; Zhong, T.; Cowling, S. J. (Liq. Cryst., 2015)

(untitled) - Mandle, R. J.; Davis, E. J.; Archbold, C. T.; Cowling, S. J.; Goodby, J. W. (J. Mater. Chem. C, 2014)